INDY—From Flies to Worms, Mice, Rats, Non-Human Primates, and Humans - Mishra, Dushyant; Kannan, Kavitha; Meadows, Kali; Macro, Jacob; Li, Michael; Frankel, Stewart; Rogina, Blanka (Frontiers in Aging, 2021)
I’m Not Dead Yet (Indy) is a fly homologue of the mammalian SLC13A5 (mSLC13A5) plasma membrane citrate transporter, a key metabolic regulator and energy sensor involved in health, longevity, and disease. Reduction of Indy gene activity in flies, and its homologs in worms, modulates metabolism and extends longevity. The metabolic changes are similar to what is obtained with caloric restriction (dietary restriction). Similar effects on metabolism have been observed in mice and rats. As a citrate transporter, INDY regulates cytoplasmic citrate levels. Indy flies heterozygous for a P-element insertion have increased spontaneous physical activity, increased fecundity, reduced insulin signaling, increased mitochondrial biogenesis, preserved intestinal stem cell homeostasis, lower lipid levels, and increased stress resistance. Mammalian Indy knockout (mIndy-KO) mice have higher sensitivity to insulin signaling, lower blood pressure and heart rate, preserved memory and are protected from the negative effects of a high-fat diet and some of the negative effects of aging. Reducing mIndy expression in human hepatocarcinoma cells has recently been shown to inhibit cell proliferation. Reduced Indy expression in the fly intestine affects intestinal stem cell proliferation, and has recently been shown to also inhibit germ cell proliferation in males with delayed sperm maturation and decreased spermatocyte numbers. These results highlight a new connection between energy metabolism and cell proliferation. The overrall picture in a variety of species points to a conserved role of INDY for metabolism and health. This is illustrated by an association of high mIndy gene expression with non-alcoholic fatty liver disease in obese humans. mIndy (mSLC13A5) coding region mutations (e.g., loss-of-function) are also associated with adverse effects in humans, such as autosomal recessive early infantile epileptic encephalopathy and Kohlschütter−Tönz syndrome. The recent findings illustrate the importance of mIndy gene for human health and disease. Furthermore, recent work on small-molecule regulators of INDY highlights the promise of INDY-based treatments for ameliorating disease and promoting healthy aging.